Online SHM Optical Scanning Data Exchange - Hernández Perdomo, W. (2017)
Online SHM Optical Scanning Data Exchange can provide practical monitoring and useful information for people associated with Structural Health Monitoring. The information obtained from the monitoring process can contain data about the behavior of structures such as bridges, buildings, tunnels or dams. The data analysis of structures behavior regarding the vibration of theirs elements and displacements may provide preventive decisions to avoid their deterioration or even collapses. This paper focus on migrating an optical scanning prototype from on-site measurement storage and further monitoring tasks, to an online data exchange from optical scanning to a remote computational station using a Cloud Computing Service and a Raspberry Pi as a data acquisition system, in order to enable an Optical Scanning System Prototype for Large-Scale 3D Monitoring on field environment.